A nonlinear polycrystalline ice elastoplastic contact model and its application - Xiaolin Li; Ge Zhang; Xinyi Chen (PLoS ONE, 2025)
With the gradual warming of the global climate, the possibility and risk of large-scale sliding and collapse disasters of glaciers, large ice sheets, and thicker ice sheets have increased. Using the discrete element numerical method to analyze glacier stability is of great importance for polar disaster prediction. A contact model, which can accurately reflect the mechanical properties of polycrystalline ice, is key to conducting a discrete element numerical simulation of glacier stability. Based on the results of conventional triaxial compression tests on polycrystalline ice, we proposed an elastoplastic contact model. A custom contact model subroutine (dynamic link library [DLL]) for the two-dimensional particle flow code (PFC2D) was generated using C++. A self-defined contact model subroutine (DLL) was used to simulate the biaxial shear of the flexible film at different temperatures. The numerical simulation results were in good agreement with the experimental results. The proposed contact model accurately reflected the deformation characteristics of polycrystalline ice. Finally, a discrete element numerical simulation of glacier ice collapse was conducted. An elastoplastic contact model of polycrystalline ice was established to provide a numerical basis for glacier stability analysis and multi-field coupling research.